Association between solid cooking fuel and cognitive decline: Three nationwide cohort studies in middle-aged and older population - Tingting Xu; Xiaoying Ye; Xiaoli Lu; Guohui Lan; Mengying Xie; Zelin Huang; Tinggui Wang; Jieyu Wu; Zhiying Zhan; Xiaoxu Xie (Environment International, 2023)
Background: Household solid-fuel burning contributes to indoor air pollution and is linked to poor cognitive function, but how solid cooking fuel use leads to cognitive decline over time is not well elaborated. Objective: We examine the associations of solid cooking fuel with cognitive function among three nationally representative cohorts. Methods: This study uses data from the 2010–2018 China Family Panel Studies (CFPS), the 2011–2018 China Health and Retirement Longitudinal Study (CHARLS) and the 2003–2015 Mexican Health and Aging Study (MHAS) in adults over the age of 50. Time varying Cox model was conducted to measure the association between cooking fuel types and cognitive decline. Mediation analysis was used to estimate the potential mediation effects on the associations of cooking fuel types with cognitive decline risk. Results: Respondents in CFPS, CHARLS, and MHAS relied on solid cooking fuel at baseline approximately 56 %, 51 %, and 12 %, respectively. Using solid fuel was consistently associated with higher risk of cognitive decline in three cohorts (CFPS: HR = 1.300 [95 % CI: 1.201, 1.407], CHARLS: HR = 1.179 [95 % CI: 1.059, 1.312], MHAS: HR = 1.237 [95 % CI: 1.123, 1.362]). Compared to those with persistent solid fuel, persistent clean fuel and change from solid fuel to clean fuel were associated with a lower risk of cognitive decline. Hypertension, diabetes, physical activity, dyslipidemia and high-density lipoprotein cholesterol (HDL-C) may partially mediate the cognitive decline caused by solid fuel use. Of the cognitive decline burden, 18.23 % (95 % CI: 12.21 %, 24.73 %) in CFPS, 8.90 % (95 % CI: 2.93 %, 15.52 %) in CHARLS and 2.92 % (95 % CI: 1.52 %, 4.46 %) in MHAS of cognitive decline cases attributable to solid cooking fuel use. Conclusion: The use of solid cooking fuel is associated with a higher risk of cognitive decline. It is essential to promote the expanded use of clean fuel to protect cognitive health.